Methylation status of TUSC3 is a prognostic factor in ovarian cancer. Issue 5 (23rd October 2012) - Pils, Dietmar; Horak, Peter; Vanhara, Petr; Anees, Mariam; Petz, Michaela; Alfanz, Angela; Gugerell, Alfred; Wittinger, Michael; Gleiss, Andreas; Auner, Veronika; Tong, Dan; Zeillinger, Robert; et al.
Abstract BACKGROUND. Current prognostic information in ovarian cancer is based on tumor stage, tumor grade, and postoperative tumor size. Reliable molecular prognostic markers are scarce. In this article, the authors describe epigenetic events in a frequently deleted region on chromosome 8p22 that influence the expression of tumor suppressor candidate 3 (TUSC3), a putative tumor suppressor gene in ovarian cancer. METHODS. Messenger RNA expression and promoter hypermethylation of TUSC3 were studied in ovarian cancer cell lines and in tumor samples from 2 large, independent ovarian cancer cohorts using polymerase chain reaction‐based methods. RESULTS. The results indicated that TUSC3 expression is decreased significantly because of promoter methylation in malignant ovarian tumors compared with benign controls. Almost 33% of ovarian cancer samples had detectable TUSC3 promoter methylation. Furthermore, methylation status of the TUSC3 promoter had a significant and independent influence on progression‐free and overall survival. CONCLUSIONS. TUSC3 hypermethylation predicted progression‐free and overall survival in ovarian cancer. The current observations suggested a role for N‐glycosylating events in ovarian cancer pathogenesis in general and identified the epigenetic silencing of TUSC3 as a prognostic factor in this disease. Cancer 2013. © 2012 American Cancer Society.